2014
DOI: 10.3928/01477447-20140924-57
|View full text |Cite
|
Sign up to set email alerts
|

Return to Sport After Hip Arthroscopy: Aggregate Recommendations From High-volume Hip Arthroscopy Centers

Abstract: Hip arthroscopy is a minimally invasive surgical technique often performed in athletes who want an expeditious return to sport. To the authors' knowledge, no studies in the literature provide a time frame or criteria for return to sport after hip arthroscopy. The purpose of this study was to develop an aggregate recommendation for return to sport after hip arthroscopy based on data assimilated from high-volume hip arthroscopy centers. Twenty-seven orthopedic surgeons from high-volume hip arthroscopy centers co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 13 publications
(18 reference statements)
1
33
0
Order By: Relevance
“…Additional factors influencing return to sport include the sport type, level of competition, and severity of the intra-articular hip damage. 14 This information demonstrates that a multitude of factors contribute to patient outcomes and return to sport, which also highlights the complexity in predicting these outcomes. Therefore, a detailed understanding of the predictors of both superior and inferior outcomes of athletic function after arthroscopic surgery for FAIS is imperative for treating surgeons.…”
Section: Introductionmentioning
confidence: 91%
“…Additional factors influencing return to sport include the sport type, level of competition, and severity of the intra-articular hip damage. 14 This information demonstrates that a multitude of factors contribute to patient outcomes and return to sport, which also highlights the complexity in predicting these outcomes. Therefore, a detailed understanding of the predictors of both superior and inferior outcomes of athletic function after arthroscopic surgery for FAIS is imperative for treating surgeons.…”
Section: Introductionmentioning
confidence: 91%
“…The questionnaire was delivered via email to 34 hip surgeons identified as high volume hip surgeons. Based on the previous work of Domb et al, high volume hip surgeons were defined as those who perform a minimum of 50 hip arthroscopies a year [12]. This survey took into account hip arthroscopists renown for the volume of hip scopes they perform each year and more importantly, for their distinguished and established positions in the academic field of hip scopes as they are all very active members of scientific community such as ISHA (board members and committee directors) ISAKOS (Hip and groin committee) and ESSKA (Hip committee members).…”
Section: Methodsmentioning
confidence: 99%
“…17 While the side bridge does not measure pelvic control in the sagittal plane, it may be a surrogate measure of overall trunk endurance, and our findings might suggest that trunk muscle performance bilaterally is an important target reconstruction, 14,16 although hopping tests do not yet have reported validity in a post-hip arthroscopy population. 26 It has been reported that some patients have achieved return to sport between 12 and 20 weeks postsurgery, 12 while up to 75% of patients have returned to sport by 12 months. 4 Our study indicates that significant impairments still exist in single hopping on both sides 12 to 24 months following hip arthroscopy.…”
mentioning
confidence: 99%